Commemorative Landscapes to the Missing: The HMAS Sydney II Memorial - Stephens, John (Routledge, 2014)
The sinking of Australian cruiser HMAS Sydney II in a mutually destructive battle with the German HSK Kormoran off the Western Australian coast in November 1941 was a national tragedy amplified by the failure to find the wrecked cruiser until 2008. Uncertainty over the ship’s fate and its crew led to a frenzy of speculation. Parallel to this public interest was the will to commemorate the missing sailors somewhere along the coastline opposite the battle site. And so the HMAS Sydney II Memorial in Geraldton, a highly symbolic and emotive memory landscape, was built. This paper explores this memorial as a memorial landscape to ‘the missing’—a special category of military death—and examines how this landscape offers closure to the trauma of survivors and subsequent generations by providing a narrative landscape that attempts to heal distress caused by an absent body.